(untitled) (Dhaka University Journal of Biological Sciences, 2024)
Voice therapy in improving the voice quality of vocal fold nodule patients has evidentiary support. This study aimed to investigate the efficacy of voice therapy for Bangladeshi patients (N=30) with vocal fold nodules, as well as the factors (therapy practice and maintenance of vocal hygiene) that influence the effectiveness or outcome of voice therapy in treating vocal fold nodules. This study was an observational cohort study of 30 Bangladeshi adult patients with vocal fold nodules (mean age=41; SD= 8.78). Before and after voice therapy, Phonation exercises and narrative-telling tasks were used to elicit voice features, and the size of vocal fold nodules was observed through Fiber Optic Laryngoscopy (FOL). The data was statistically analyzed using the percentage/proportion test and Fisher’s exact test to demonstrate the success of voice therapy and the factors impacting the therapy’s efficacy. The findings indicated that voice therapy was successful for most participants (87%). Practicing therapy regularly and maintaining vocal hygiene had an impact on therapy success.